Model Kooperatif Jigsaw untuk Meningkatkan Aktivitas Belajar Siswa pada Materi Pencemaran dan Kerusakan Lingkungan - Muhammad Yassir (Biotik, 2015)
The purposes of this research was to know students’ learning activity at class VII MTsN Kuta Baro, Aceh Besar in the concept of environmental pollution and destruction by using cooperative jigsaw model. This is a quasi-experimental research with pretest – post test control group design. It has been conducted at MTsN Kuta Baro, Aceh Besar district at class VII-4 by using cooperative jigsaw model and class VII-3 by using conventional learning. The data were collected by using observation sheet and then analyzed by using average and percentage techniques. The results showed that the percentage of students’ learning activity in the experimental class in forming the group was 98%, learning material in group was 93% dan discussing was 89%. Meanwhile, in control class, the activity in forming the group was 88%, learning material in group was 85% and discussing was 83%. It can be concluded that students’ leaning activity in the concept of environmental pollution and destruction by using cooperative jigsaw model (average was 85.81) was higher than conventional learning activity (average was 78.16).